Low-cost alternatives for improving thermal comfort in residences (Research, Society and Development, 2025)
In recent years, due to the rise in global temperatures, there has been a growing need to find solutions that improve thermal comfort in buildings. This work therefore aimed to analyze low-cost alternatives for its promotion, demonstrate the effectiveness of thermal insulation in buildings, and implement the selected measures in a local residence. In the study, viable methods such as thermal insulation and cool roofs were researched. As the work progressed, these measures were found to be effective in reducing heat flow in climates similar to that of the city. Consequently, the decision was made to apply white paint on the roof due to its high albedo, as well as to use Expanded Polystyrene (EPS) for insulation. To test the effectiveness of these techniques, experiments were conducted using boxes that simulated residences. A comparison was made between a conventional house, one with EPS insulation, and another with a white-painted roof in addition to the insulation. The results showed that both the insulation and the roof painting significantly reduced indoor temperatures. Based on these findings, a room in a local house was renovated, with its roof covered with EPS. After the intervention, the resident reported a more pleasant thermal sensation and, consequently, less use of devices to cool the room, which confirmed the effectiveness of the measures adopted. Therefore, the study concludes that the use of EPS and cool roofs are efficient and accessible alternatives to promote thermal comfort in houses.